Answer:
![( (5)/(11) \:</strong><strong>,</strong><strong> - (3)/(11) )](https://img.qammunity.org/2021/formulas/mathematics/college/e9en3svz0stza9rlagn70rnl59ui2moauk.png)
Explanation:
6x - y = 3
4x + 3y = 1
Solve the equation for y
y = -3 + 6x
4x + 3y = 1
Substitute the given value of y into the equation
4x + 3y = 1
plug the value
![4x + 3( - 3 + 6x) = 1](https://img.qammunity.org/2021/formulas/mathematics/college/dj4tmgwxb1so82b8mpyhvqermiw0oxisni.png)
Distribute 3 through the parentheses
![4x - 9 + 18x = 1](https://img.qammunity.org/2021/formulas/mathematics/college/rdsdcbyy6lw0g14nwne334g3ikck8a6olc.png)
Collect like terms
![22x - 9 = 1](https://img.qammunity.org/2021/formulas/mathematics/college/d36zdcr00gb7rstwcd7ud18ewmsvsxum3d.png)
Move constant to R.H.S and change its sign
![22x = 1 + 9](https://img.qammunity.org/2021/formulas/mathematics/college/eqmwbosqki9l52j2ejzikarh0qfwpd0orb.png)
Calculate the sum
![22x = 10](https://img.qammunity.org/2021/formulas/mathematics/college/8pvd0bx55e7yfxvn0ykdilnhu36s3shb82.png)
Divide both sides of the equation by 22
![(22x)/(22) = (10)/(22)](https://img.qammunity.org/2021/formulas/mathematics/college/sjndajy94r9fghp3hfze44ujya06eazgs4.png)
Calculate
![x = (5)/(11)](https://img.qammunity.org/2021/formulas/mathematics/college/44io8wumvfg87syv8erx5crddowlfsvj2q.png)
Now, substitute the given value of x into the equation
y = -3 + 6x
![y = - 3 + 6 * (5)/(11)](https://img.qammunity.org/2021/formulas/mathematics/college/kwb19wxcvz4bvtd1xpc62qmr1kx6dyzilu.png)
Solve the equation for y
![y = - (3)/(11)](https://img.qammunity.org/2021/formulas/mathematics/college/pxv3q47q05jyxszn6g27wb9d9v16popopq.png)
The possible solution of the system is the ordered pair ( x , y )
![(x </strong><strong>,</strong><strong>\: y) = ( (5)/(11) </strong><strong>,</strong><strong>\: - (3)/(11) )](https://img.qammunity.org/2021/formulas/mathematics/college/7sa6idxykmh8b93ixmuvq4mmsk9j4tmbis.png)
-----------------------------------------------------------
Check if the given ordered pair is the solution of the system of equations
![6 * (5)/(11) - ( - (3)/(11) ) = 3](https://img.qammunity.org/2021/formulas/mathematics/college/cfjouuttwthfobl8qb9or919ob36pbw10g.png)
![4 * (5)/(11 ) + 3 * ( - (3)/(11) ) = 1](https://img.qammunity.org/2021/formulas/mathematics/college/ib82l6762jfnv4m721vxdvhd2z66ch880t.png)
Simplify the equalities
![3 = 3](https://img.qammunity.org/2021/formulas/mathematics/college/nnvord9d5l48ejtcgg6p9ag1oqfqs44kiu.png)
![1 = 1](https://img.qammunity.org/2021/formulas/mathematics/college/aypnuioaoqbt6628hpcbqzp68a1pqjty1t.png)
Since all of the equalities are true , the ordered pair is the solution of the system
![( \: x </strong><strong>,</strong><strong>\: y \: ) = ( (5)/(11) \:</strong><strong>,</strong><strong> - (3)/(11) )](https://img.qammunity.org/2021/formulas/mathematics/college/l68gq7901tva6vu8u9qv5bi3weadbta9s5.png)
Hope this helps..
Best regards!!